Resource theft in tropical forest communities: implications for nontimber management, livelihoods, and conservation - Duchelle, Amy E.; Cronkleton, P.; Kainer, K.A.; Guanacoma, G.; Gezan, S. (2011)
Increased devolution of forest ownership and management rights to local control has the potential to promote both conservation and livelihood development in remote tropical regions. Such shifts in property rights, however, can generate conflicts, particularly when combined with rapidly increasing values of forest resources. We explored the phenomenon of Brazil nut (Bertholletia excelsa) theft in communities in Western Amazonia. Through interviews with 189 Brazil nut collectors in 12 communities in Bolivia and Brazil and participation in the 2006 and 2007 harvests, we quantified relative income derived from Brazil nuts, reported nut thefts, and nut collection and management practices. We found a much greater incidence of reported Brazil nut thefts in Pando, Bolivia than in the adjacent state of Acre, Brazil. Our analyses suggest that three factors may have affected nut thefts in the forest: (1) contrasts in the timing and process of formally recognizing property rights, (2) different historic settlement patterns, and (3) varying degrees of economic dependence on Brazil nuts. Threat of theft influenced Brazil nut harvest regimes, with potentially long-term implications for forest-based livelihoods, and management and conservation of Brazil nut-rich forests in Western Amazonia.